2022
DOI: 10.1186/s12978-022-01510-x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to family planning messages and teenage pregnancy: results from the 2017 Philippine National Demographic and Health Survey

Abstract: Background Teenage pregnancy is known to have physical, emotional, and psychosocial effects. Because of these risks, family planning and contraception messages have been disseminated in various forms of media, but their association with teenage pregnancy has not been studied previously in the Philippines. This study aims to examine the association between exposure to various family planning and contraception messages disseminated in various media channels and pregnancy among Filipino women aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Newspapers may reach a more literate audience who is more likely to engage with and act upon the information provided [92]. Moreover, previous studies have reported mixed results regarding the in uence of media-based family planning messages on adolescent pregnancy risk, with some studies showing a reduction in risk with exposure to such messages, while other studies have suggested an increase in risk [57][58][59]. It is therefore crucial for policymakers to consider the diverse needs and preferences of adolescents when designing and implementing media-based family planning interventions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Newspapers may reach a more literate audience who is more likely to engage with and act upon the information provided [92]. Moreover, previous studies have reported mixed results regarding the in uence of media-based family planning messages on adolescent pregnancy risk, with some studies showing a reduction in risk with exposure to such messages, while other studies have suggested an increase in risk [57][58][59]. It is therefore crucial for policymakers to consider the diverse needs and preferences of adolescents when designing and implementing media-based family planning interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, adolescent pregnancy may be in uenced by the unavailability of contraception at health institutions [44]. Furthermore, the provision of messages on contraception and family planning via media platforms such as radio, television, and newspapers or magazines by organizations such as ministries of health can reduce or increase the risk of adolescent pregnancy [57][58][59] Environmental level Page 7/30…”
Section: Organizational Levelmentioning
confidence: 99%
“…Ang mga ina sa murang edad ay mas malamang na sumailalim sa mga iligal at hindi ligtas na pagpapalaglag na maaaring magdulot ng sakit o maging kamatayan (Melgar et al, 2018). Bukod dito, ang mga ina sa ganitong edad ay may mas mataas na panganib na magkaroon ng iba't ibang komplikasyon sa kalusugan tulad ng eclampsia, puerperal endometritis, at systemic infections kumpara sa mas matatandang ina (Pepito et al, 2022).…”
unclassified